Analysis of structural variations and effects of the national volume-based procurement policy on inpatient costs: a real world study of osteoporotic hip fractures in Shanghai, China - Yan, Jing; Qin, Qiujun; Fang, Xinye; Li, Fen; Zhu, Bifan (Frontiers in Public Health, 2025)
BackgroundAs one of the most severe clinical manifestations of osteoporosis, osteoporotic hip fractures often require surgical treatment and result in high medical costs. The hospitalization expenses for patients with osteoporotic hip fractures in China have been on the rise; however, there are few reports on the structural variations in hospitalization costs for these patients and the correlation between total and individual expenses. This research aims to analyze the structure of hospitalization costs and their changes over an extended period in Shanghai, China, and to investigate the impact of the national volume-based procurement (NVBP) policy on costs associated with osteoporotic hip fractures.MethodsData were obtained from the Shanghai Health Statistics Center, which includes hospitalization records for patients at all medical institutions in Shanghai from January 2017 to December 2022. Structural variation analysis was utilized to assess the shifts in yearly hospitalization cost composition, while new gray correlation analysis was employed to explore the degree of association between individual and total costs across both overall and various levels of hospitals. Additionally, we evaluated the effects of the NVBP on total and individual hospitalization costs using interrupted time series analysis.ResultsWhile there was a decline in 2022, medical consumable costs accounted for over 59% of total inpatient costs for osteoporotic hip fractures and consistently demonstrated the highest correlation with total hospitalization costs in Shanghai from 2017 to 2021. Drug costs not only had the highest contribution rate to overall inpatient expenses during the years 2017–2018 (44.22%) and 2020–2021 (36.76%) but also held the top position in the contribution rate of structural variation (CRSV) from 2017 to 2022 (45.77%). The stratification results at the hospital level indicated that drug costs in tertiary and secondary hospitals declined over 6 years, while primary hospitals only saw reductions in a few years. Furthermore, medical consumable costs for tertiary and secondary hospitals decreased in 2021–2022, with CRSVs of 23.36 and 37.91%; however, primary hospitals had higher medical consumable costs during this period. After the NVBP policy was implemented, total hospitalization costs significantly decreased by 5,022.088 yuan (p < 0.001). Additionally, hospitalization costs exhibited a significant downward trend over time, decreasing by 596.114 yuan after the intervention (p < 0.001). Medical consumable costs also exhibited a declining pattern regarding both immediate effects and long-term patterns after the reform, with an average decrease of 290.448 yuan (p < 0.001).ConclusionAlthough the medical consumable costs related to osteoporotic hip fractures made up the largest portion of total expenditures for inpatients, their share declined due to the implementation of the NVBP. Despite the significant structural variation in drug costs, they still represented the second-largest part of total hospitalization expenditures. Future policy should focus on addressing the rising hospitalization costs of osteoporotic hip fractures, particularly those associated with medical consumables and drugs. Besides, additional regulations should be established based on the cost structures of medical institutions at various levels.